The voting machine: The material culture of polling stations in Ghana, Kenya and Uganda - Cheeseman, N; Willis, J; Lynch, G (Editions Karthala, 2017)
Elections are characterised by different public performances of order that are enacted during campaigns and the bureaucratic processes of the polls. This paper explores a key element of the latter; namely, the material culture, and associated processes, of the polling station. It does so by looking at change and continuity in polling station practice in the post-colonial period in three African countries: Ghana, Kenya and Uganda. The analysis reveals how all three countries demonstrate significant variation in the way that leaders have conceptualised and used electoral processes, but all have nonetheless moved to very similar technologies and practices of voter identification and vote casting, which reveal significant continuities from late-colonial practice. More specifically, we argue that the colocation and technical combination of multiple items and processes have created the polling station – ideally, though not always in reality – as a bureaucratic machine, which helps to enact a particular relationship between the state and the individual citizen. In so doing, the polling station helps to create the state as a distinct entity and sphere of order, even as it creates the voter as the subject of that order. However, while polling stations are designed to produce an ideal of unmediated citizenship, practice and experience often subvert that ideal, and suggest that the state – instead of being a distinct sphere of impartial order – is profoundly entangled with society. As a result, while the polling station remains a powerful classroom, the lessons that it teaches are inconsistent and contested.